(untitled) (TAMADDUN NURI JURNALI, 2025)
The article considers the prerequisites for the emergence of banking institutions in the late XIX - early XX century and their influence in the Turkestan region. The article also analyses the socio-economic consequences of Russian banks for the local population. On the basis of sources the duality of development of Russian banks in the region is analysed: on the one hand, the banks promoted the introduction of industry in the region, and on the other hand - strengthened colonial dependence.